A profile of the future: what could HTML 5 do for HE by 2015? - Rick Ogden; Rob Aspin; Lee Griffiths (Association for Learning Technology, 2012)
HTML 5 is the most significant update of HTML in the last 10 years since XHTML was introduced. It promises a vastly improved user experience, increased browser features, cross compatibility and the ability to provide semantic content. In this paper we discuss the near future position for Higher Education in terms of technological transform, the proposed capabilities of HTML 5, and how they may change and how virtual learning environments are implemented in the future. We offer a set of education-based scenarios and how the emerging standard could benefit them. Finally we conclude with possible implementation timescales.